2016
DOI: 10.1377/hlthaff.2015.1294
|View full text |Cite
|
Sign up to set email alerts
|

Kentucky’s Medicaid Expansion Showing Early Promise On Coverage And Access To Care

Abstract: Kentucky is one of only two southern states, at the time of this writing, to have expanded Medicaid under the Affordable Care Act. The expansion raised Medicaid eligibility levels as a means to make coverage more accessible and make health care more affordable for a population likely to face financial barriers in using medical care. This article examines the first-year impact of Kentucky's Medicaid expansion on insurance coverage and access to care. Focusing on Kentucky's low-income population, we observed lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 12 publications
1
51
1
Order By: Relevance
“…[28] In a single-state review of Medicaid expansion, Benitez et al found lower rates of unmet medical needs and fewer people without routine access to healthcare. [19] Proper diagnosis and medical management of comorbidities may result in lower preoperative risk scores.…”
Section: Commentmentioning
confidence: 99%
“…[28] In a single-state review of Medicaid expansion, Benitez et al found lower rates of unmet medical needs and fewer people without routine access to healthcare. [19] Proper diagnosis and medical management of comorbidities may result in lower preoperative risk scores.…”
Section: Commentmentioning
confidence: 99%
“…Other studies have used survey data to examine the association between the ACA insurance expansions and insurance access or take‐up . Frean, Gruber, and Sommers estimated the relative contributions of different ACA provisions to observed insurance changes, finding that Medicaid enrollment among previously eligible adults accounted for half of the reduction in uninsurance attributable to the Medicaid expansion .…”
Section: Background and Research Objectivesmentioning
confidence: 99%
“…Notably, the ACA included SUD treatment as an essential health benefit within health plans and expanded parity for SUD care. 1618 It has reduced the number of uninsured Americans, particularly in Medicaid expansion states, 19,20 and reduced the number of individuals with OUD who lack insurance. 21 However, there remain no requirements that buprenorphine-prescribing physicians (BPPs, or any other medical provider) accept insurance plans for reimbursement of treatment services, raising the possibility that insured individuals cannot use their insurance benefits to pay for care.…”
Section: Introductionmentioning
confidence: 99%